ANALISIS KEMAMPUAN MATEMATIKA TERHADAP HASIL BELAJAR SISWA SMA PADA MATERI LARUTAN PENYANGGA - Tasyadri, Widia; Sihombing, Junifa Layla; Wahyu Nugraha, Asep; Andi Syahputra, Ricky; Amdayani, Susilawati (Universitas Negeri Medan, 2025)
Abstract: The purpose of this study was to determine the relationship between math skills and chemistry learning outcomes of MAN 1 Medan students. This research is quantitative using basic linear regression analysis. The sample was taken by purposive sampling and a sample of one class was selected, namely XI MIPA 2. The instrument used was a test consisting of 10 essay questions on each chemistry question sheet of buffer solution and math ability. Analysis of research instruments was carried out with qualitative analysis and hypothesis testing was carried out with correlation and determination coefficient tests. The results of data analysis showed a positive and strong relationship between math ability and chemistry learning outcomes, this is evidenced by the acquisition of a sig value of 0.00 <0.05 and a correlation coefficient of 0.809. As for the contribution of the influence of math ability on chemistry learning outcomes of 65.4% to learning outcomes and other factors affect the remaining 34.6%. Keyword: Chemistry Learning Outcomes, Math Skills, Buffer Abstrak: Tujuan dari penelitian ini adalah untuk mengetahui hubungan kemampuan matematika dan hasil belajar kimia siswa MAN 1 Medan. Penelitian ini termasuk kuantitatif dengan menggunakan analisis regresi linier dasar. Sampel diambil secara purposive sampling dan dipilih sampel dari satu kelas, yaitu XI MIPA 2. Instrumen yang digunakan ialah tes yang terdiri dari 10 soal esai pada masing-masing lembar soal kimia larutan penyangga dan kemampuan matematika. Analisis instrumen penelitian dilakukan dengan analisis kualitatif dan pengujian hipotesis dilakukan dengan uji koefien korelasi dan determinasi. Hasil analisis data menunjukkan adanya hubungan positif dan kuat antara kemampuan matematika dan hasil belajar kimia, hal ini dibuktikan dengan perolehan nilai sig 0,00< 0,05 dan koefisien korelasi sebesar 0,809. Adapun untuk kontribusi pengaruh kemampuan matematika terhadap hasil belajar kimia sebesar 65,4% terhadap hasil belajar dan faktor lain memengaruhi 34,6% sisanya. Kata Kunci: Hasil Belajar Kimia, Kemampuan Matematika, Larutan Penyangga